PENERAPAN PEMUPUKAN PADA PERTANIAN PADI ORGANIK DENGAN METODE SYSTEM OF RICE INTENSIFICATION (SRI) DI DESA SUKAKARSA KABUPATEN TASIKMALAYA - Tati Suryati Syamsudin; Sri Aktaviyani (Agroland: Jurnal Ilmu-ilmu Pertanian, 2009)
The purpose of the research was to apply sustainable fertilizing system in organic farming                 by System of Rice Intensification (SRI) method. The research was conducted at Sukarasa village, Tasikmalaya West Java. The experiments were conducted using various levels of compost (0, 5, 7.5, 10, 12.5, and 15 tons/acre) and local microorganism (LMO) with different spraying frequencies (0, 4 and 8 times) over the planting season. The results showed that there were no significant effects of yield from organic farming developed by the variety of system introduced above. This result reveals                     no positive correlation between adding more compost and LMO to the yield. The average yield was 4.29 tons/acre. The availability of organic material taken from household garbage and straw                    is 1216. 82 tons. However the need of this organic material to form compost in Sukarasa village is only 922. 35 tons per planting season.